BRIDGING SUSTAINABILITY AND POLICING TO BALINESE ORMAS CONFLICT: AN INTEGRATIVE CONCEPTUAL FRAMEWORK - Sudama, I Nyoman; Meliala, Adrianus; Laksana, Chrysnanda Dwi; Hamid, Supardi (UI Scholars Hub, 2021)
The link between sustainability and policing has not been widely discussed and systematically analyzed in conflict resolution to gain long term goals of post-conflict recovery and reconciliation. A fairly large cross-disciplinary literature has developed and proposed a multi-dimensional notion of sustainability in organizational performance including public services and law-enforcement activities. Thus, the purpose of this paper is to present a conceptual framework to bridge sustainability practices and policing activities in the background of Balinese mass organization conflict. A conceptual literature review is adopted to customize diverse connections of sustainability, policing, and hence conflict. The results of the research show that the policing activities may place a stronger focus on conflict resolution by developing sustainable conflict transformation when there are regular conflict potential and a dynamic changing environment. The primary conclusion of this paper is that the relationships between sustainability practices and policing activities rely on divergent factors, including social dynamics, culture, organizational structure, and institutional landscapes.